Living in the South, Caring in the North: Exploring Inuit Women’s Care Responsibilities - Quintal-Marineau, Magalie (The International Indigenous Policy Journal)

(untitled) (Scholarship@Western (Western University), 2020)
The increased Inuit population in Canadian Metropolitan Areas (CMA) has recently gained attention among the scientific community as well as within Inuit organizations. However, existing literature has overlooked the distinct experience of Inuit women and, more significantly, the importance of care responsibilities in understanding women’s mobility. This study examines the relocation experiences of 46 Inuit women across five CMAs, and the role care sites play in initiating women’s relocation to cities. Results show the key role caregiving responsibilities play in Inuit women’s decisions to move to southern urban areas, as dysfunctional care spaces in the North push them away from their communities, and the potential for safer care sites in the South act as a pulling factor.